Radiotherapy regimens in patients with nonmelanoma head and neck skin cancers. (22nd January 2018) - Dundar, Yusuf; Cannon, Richard B.; Hunt, Jason P.; Monroe, Marcus; Suneja, Gita; Hitchcock, Ying J.
Abstract: Background: To assess the effectiveness and outcomes of adjuvant radiotherapy regimens for nonmelanoma skin cancers (NMSC) of the head and neck, particularly for elderly patients. Methods: A retrospective review of patients with head and neck NMSC was conducted. Radiotherapy dose per fraction regimens included ≤200, 240–250, 300–400, and 500–600 cGy. Demographics, tumor characteristics, local control (LC), regional control (RC), and survival outcomes were analyzed. Results: Of the 90 patients with 140 disease sites, 76.6% were squamous cell carcinoma, 15.5% were basal cell carcinoma, and 7.7% were other histologies. The mean age at diagnosis was 72.1 years old. The most common location was preauricular (20.0%), followed by temple, scalp, cheek, and forehead. The overall LC and RC rates were 88.8% and 88.8%, respectively by patients, and 92.8% and 86.4%, respectively by treatment sites. Age, primary tumor location, T classification, N classification, overall stage, perineural invasion, comorbid disease, skull base invasion, and radiotherapy subgroup were significantly associated with disease‐free and overall survival ( P < 0.05). LC and RC were not significantly different among the radiotherapy dose subgroups. The mean survival was longer in patients treated with 240–250 cGy/fraction (50.3 months). There was no significant difference in radiotherapy toxicity between the subgroups. Conclusion: Short‐term radiotherapy regimens for patients with locally or regionally advanced head and neck NMSC appear feasible and effective, particularly in elderly patients or those that cannot tolerate the length of standard regimens.